Prognostic analysis of high-flow nasal cannula therapy and non-invasive ventilation in mild to moderate hypoxemia patients and construction of a machine learning model for 48-h intubation prediction—a retrospective analysis of the MIMIC database - Fu, Wei; Liu, Xiaoqing; Guan, Lili; Lin, Zhimin; He, Zhenfeng; Niu, Jianyi; Huang, Qiaoyun; Liu, Qi; Chen, Rongchang (Frontiers in Medicine, 2024)
Background：To investigate the clinical outcome between high flow nasal cannula (HFNC) and non-invasive ventilation (NIV) therapy in mild to moderate hypoxemic patients on the first ICU day, and to develop a predictive model of 48-hour intubation. Methods: The study included adult patients from the MIMIC III and IV databases who first initiated HFNC or NIV therapy due to mild to moderate hypoxemia (100